2017
DOI: 10.1002/mus.25413
|View full text |Cite
|
Sign up to set email alerts
|

Late‐onset pompe disease in Iran: A clinical and genetic report

Abstract: This is a comprehensive report of LOPD in Iranian patients. Distinct phenotypic and genotypic features in this population are highlighted. Muscle Nerve 55: 835-840, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
0
4
1
Order By: Relevance
“…However, the results reported for diagnostic delay vary considerably between countries. For instance, the diagnostic delay in cohorts from Austria, China, and Iran were 7.4, 5, and 3.3 years, respectively (17)(18)(19). Therefore, in the present study, the diagnostic delay was shorter than those previously observed.…”
Section: Discussioncontrasting
confidence: 49%
“…However, the results reported for diagnostic delay vary considerably between countries. For instance, the diagnostic delay in cohorts from Austria, China, and Iran were 7.4, 5, and 3.3 years, respectively (17)(18)(19). Therefore, in the present study, the diagnostic delay was shorter than those previously observed.…”
Section: Discussioncontrasting
confidence: 49%
“…A cohort study in Austria revealed an even lower prevalence of 1:351,000 of Pompe disease (including both LOPD and infantile forms) [18]. Thus, LOPD is a rare disease, and the low prevalence may be one explanation for the long diagnostic delay of almost 13 years in our study, 7.4 years in the Austrian cohort [18], about 5 years in a Chinese patient group [19] and 3.3 years in an Iranian cohort [20]. Furthermore, the clinical presentation is variable and can be mild and non-specific, especially at the beginning of the disease.…”
Section: Lopd Is a Rare Disease And Associated With A Long Diagnosticmentioning
confidence: 41%
“…Case 2: This is an infant with two heterozygous pathogenic variants. The c.1979G>A variant has been associated with both IOPD and LOPD [ 35 , 36 ]; and the c.1754+1_1754+12delinsCCA variant has no reported link to Pompe disease but was deemed as disease-causing in general [ 37 ]. Confirmatory tests found reduced GAA enzyme activity and mildly elevated Hex4.…”
Section: Resultsmentioning
confidence: 99%